2021
DOI: 10.1186/s12870-021-03010-9
|View full text |Cite
|
Sign up to set email alerts
|

Microscopy and chemical analyses reveal flavone-based woolly fibres extrude from micron-sized holes in glandular trichomes of Dionysia tapetodes

Abstract: Background Dionysia tapetodes, a small cushion-forming mountainous evergreen in the Primulaceae, possesses a vast surface-covering of long silky fibres forming the characteristic “woolly” farina. This contrasts with some related Primula which instead form a fine powder. Farina is formed by specialized cellular factories, a type of glandular trichome, but the precise composition of the fibres and how it exits the cell is poorly understood. Here, using a combination of cell biology (electron and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…We also found that blue fluorescence was mainly concentrated in the phloem of the stem, which is direct evidence for the phloem transport of NPs. Trichomes were thought to be possible pathways for engineered nanoparticles to enter into leaves . Interestingly, we also found PS-Eu inside the trichomes of leaves (Figure S23).…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…We also found that blue fluorescence was mainly concentrated in the phloem of the stem, which is direct evidence for the phloem transport of NPs. Trichomes were thought to be possible pathways for engineered nanoparticles to enter into leaves . Interestingly, we also found PS-Eu inside the trichomes of leaves (Figure S23).…”
Section: Resultsmentioning
confidence: 63%
“…Trichomes were thought to be possible pathways for engineered nanoparticles to enter into leaves. 66 Interestingly, we also found PS-Eu inside the trichomes of leaves (Figure S23). However, whether these NPs were internalized directly by the trichomes or transferred inside the trichomes after internalization by the cuticle remains to be further explored.…”
Section: Charge Controlled Internalization Of Nps Into Leavesmentioning
confidence: 66%
See 1 more Smart Citation
“…15 In a vial, dry farinose exudate reassembles into long threads as observed for Primula florindae Ward (see Figure S1), resembling the in vivo observed extrusion from Dionysia glandular hairs. 16…”
Section: History Of Flavonementioning
confidence: 99%
“…They may also have shiny surface regions (wax, surface crust and reflective hairs) that give glare with epi-illumination. These types of plants have worked very well for cryoSEM, and their habitation in cold, dry climates appears to greatly limit the amount of exogenous (surface) ice that forms during plunge-freezing [35][36][37].…”
Section: Plant Anatomy Patterning and Tissue Organisationmentioning
confidence: 99%